Resuscitative endovascular balloon occlusion of the aorta for thoracic trauma: A translational swine study. Issue 3 (September 2020) - Glaser, Jacob J.; Neidert, Leslie E.; Morgan, Clifford G.; Brenner, Megan; Stigall, Kyle S.; Cardin, Sylvain
Abstract : ABSTRACT: Noncompressible torso hemorrhage in trauma is particularly lethal. Resuscitative endovascular balloon occlusion of the aorta (REBOA) has the potential to stabilize these patients, but currently is contraindicated for major thoracic bleeding. The goal of this study was to evaluate the effect of REBOA on the hemodynamic and metabolic profile as well as its effect on early survival in a porcine model of thoracic hemorrhage and shock. METHODS: Forty-eight male Yorkshire swine (60–80 kg) underwent 30% hemorrhage and were randomized to three thoracic injuries, with and without zone 1 REBOA occlusion: pulmonary parenchymal injury, thoracic venous injury, or subclavian artery injury. Following hemorrhage, thoracic injuries were induced (time of major thoracic injury) and allowed to bleed freely. The REBOA groups had zone 1 occlusion after the thoracic injury, with deflation at the end of prehospital. All groups had whole blood resuscitation at the end of prehospital and were euthanized at end of the hospital care phase. Survival, total blood loss, mean arterial pressure, end-tidal CO2, and arterial blood gas parameters were analyzed. Statistical significance was determined by t tests and two-way repeated-measures analysis of variance. RESULTS: The use of REBOA improved the hemodynamics in all three injury patterns, with no differences observed in the outcomes of short-term survival and thoracic blood loss between the REBOA and non-REBOA groups. All groups showed equivalent changes in markers of shock (pH, HCO3, and base excess) prior to resuscitation. CONCLUSION: In this animal study of hemorrhage and major thoracic bleeding, the addition of zone 1 REBOA did not significantly affect short-term survival or blood loss, while providing hemodynamic stabilization. Therefore, in noncompressible thoracic bleeding, without immediate surgical capability, long-term outcomes may be improved with REBOA, and thoracic hemorrhage should not be considered contraindications to REBOA use.